Precious Metals Supported on Alumina and Their Application for Catalytic Aqueous Phase Reforming of Glycerol - Kiky Corneliasari Sembiring; Anis Kristiani; Fauzan Aulia; Luthfiana Nurul Hidayati; Silvester Tursiloadi (Indonesian Journal of Chemistry, 2015)
The high cost of Pt based catalyst for aqueous phase reforming (APR) reaction makes it advantageous to develop less cost of other metals for the same reaction. APR is hydrogen production process from biomass-derived source at mild condition near 500 K and firstly reported by Dumesic and co-worker. The use of hydrogen as environmentally friendly energy carrier has been massively encouraged over the last year. When hydrogen is used in fuel cell for power generation, it produces a little or no pollutants. The aim of this study is to study the effect of some precious metal catalysts for APR process. Due to investigation of metal catalysts for APR process, four precious metals (Cu, Co, Zn, Ni) supported on γ-Al2O3 with 20% feeding amount have been successfully prepared by impregnation method. Those precious metals were identified as promising catalysts for APR. The catalysts were characterized by N2 physisorption at 77 K, X-Ray Diffraction (XRD) and Fourier Transform-Infra Red (FT-IR). The catalytic performance was investigated at 523 K and autogenous pressure in a batch reactor with glycerol concentration of 10%. The gaseous hydrogen product was observed over the prepared catalysts by GC. It was found that performance of catalysts to yield the hydrogen product was summarized as follow Cu/γ-Al2O3 > Co/γ-Al2O3 > Zn/γ-Al2O3 > Ni/γ-Al2O3.